Apports terrigènes et sédimentation épicontinentale en régime tropical-équatorial sud-américain (Guyanes, Colombie caraïbe et Pacifique) : paléogéographie et paléoclimatologie depuis le dernier Maximum Glaciaire. - Michel Pujos; Ana Pascual (Physio-Géo)
Sedimentary and paleogeographic models of epicontinental deposits are presented on three regions of South America; one stable (Guianas) and two others with neotectonic activity (Caribean and Pacific coasts of Colombia). Reef barrier, fluvial sands, and authigenesis process characterized the Last Glacial maximum (LGM 30000 to 20000 years 14-C BP). During the end of Pleistocene – early Holocene rare detrital transgressive sequences, reworking and scattering deposits are controlled by active erosion. At this time, during slower breaks on water rising, coastal deposits, clastic minerals, and bioclasts are settling by winnowing. About 5000 years BP the transgression is stopped and occur alluvial aggradation and deltaic progradation. Fine particulate material of Andean rivers is converted in dispersal oceanic systems controlled by climatic and hydrodynamic conditions but also sedimentary terrigenous prisms. During the end of Holocene, changes on epicontinental clay assemblages are linked to evolutionary climatic conditions and paleo-niños events (ENSO).